The resilience of traditional communities in the modern era: a case study of kentrung art in Java, Indonesia - Agus Yuwono; Dhoni Zustiyantoro; Widodo; Sungging Widagdo; Mukhammad Nur Rokhim (Cogent Arts & Humanities)
Kentrung is the art of singing traditional poems that use traditional music in one piece as entertainment and ritual. As a traditional Javanese art living in modernisation, kentrung symbolises courage and tenacity in facing challenges. In Indonesia, kentrung is crucial, especially for coastal Javanese communities because it has various functions, including the institutional function of Javanese society. This article discusses the role of kentrung art in depicting the resilience of Javanese social institutions. Through a social semiotics approach, this research shows how kentrung is an integral part of the daily life of Javanese people, not only as an expression of traditional Javanese music, but also as a medium of expression and a symbol of courage in facing trials. By analysing the musical practices and narratives of the people around the kentrung, this article describes the kentrung as a reflection of the courage and cultural resilience of the Javanese people in facing the changes and challenges of the times. This research ultimately shows that amid rapid social change, mainly due to the influence of modernisation and industrialisation, kentrung art can continue to survive because it has a social function and role.